Shape‐Changing DNA‐Linked Nanoparticle Films Dictated by Lateral and Vertical Patterns. Issue 13 (19th February 2022) - Kim, Jongwook; Lee, Sunghee; Choi, Jisu; Baek, Kyungnae; Shim, Tae Soup; Hyun, Jerome Kartham; Park, So‐Jung
Abstract: The self‐assembly of nanoscale building blocks into complex nanostructures with controlled structural anisotropy can open up new opportunities for realizing active nanomaterials exhibiting spatiotemporal structural transformations. Here, a combination of bottom‐up DNA‐directed self‐assembly and top‐down photothermal patterning is adopted to fabricate free‐standing nanoparticle films with vertical and lateral heterogeneity. This approach involves the construction of multicomponent plasmonic nanoparticle films by DNA‐directed layer‐by‐layer (LbL) self‐assembly, followed by on‐demand lateral patterning by the direct photothermal writing method. The distinct plasmonic properties of nanospheres and nanorods constituting the multidomain films enable photopatterning in a selective domain with precisely controlled vertical depths. The photopatterned films exhibit complex morphing actions instructed by the lateral and vertical patterns inscribed in the film as well as the information carried in DNA. Abstract : The combination of top‐down plasmonic photopatterning and bottom‐up DNA‐based self‐assembly is used to fabricate free‐standing nanoparticle films encoded with instructions for dynamic shape changes. The distinct plasmonic properties of the incorporated nanoparticles enable on‐demand lateral patterning with 3D selectivity, which, in turn, allows for fine control over the structure and morphing actions of DNA‐linked nanoparticle films.